Sequence of the Essex-Lopresti lesion—a high-speed video documentation and kinematic analysis. (April 2014) - Wegmann, Kilian; Engel, Karsten; Burkhart, Klaus J; Ebinger, Marc; Holz, Robert; Brüggemann, Gert-Peter; Müller, Lars P
<x xml:space="preserve">Abstract</x> Background and purpose — The pathomechanics of the Essex-Lopresti lesion are not fully understood. We used human cadavers and documented the genesis of the injury with high-speed cameras. Methods — 4 formalin-fixed cadaveric specimens of human upper extremities were tested in a prototype, custom-made, drop-weight test bench. An axial high-energy impulse was applied and the development of the lesion was documented with 3 high-speed cameras. Results — The high-speed images showed a transversal movement of the radius and ulna, which moved away from each other in the transversal plane during the impact. This resulted into a transversal rupture of the interosseous membrane, starting in its central portion, and only then did the radius migrate proximally and fracture. The lesion proceeded to the dislocation of the distal radio-ulnar joint and then to a full-blown Essex-Lopresti lesion. Interpretation — Our findings indicate that fracture of the radial head may be preceded by at least partial lesions of the interosseous membrane in the course of high-energy axial trauma.